Evening Primrose (Oenothera biennis) Biological Activity Dependent on Chemical Composition - Magdalena Timoszuk; Katarzyna Bielawska; Elżbieta Skrzydlewska (MDPI AG, 2018)
Evening primrose (Oenothera L.) is a plant belonging to the family Onagraceae, in which the most numerous species is Oenothera biennis. Some plants belonging to the genus Oenothera L. are characterized by biological activity. Therefore, studies were conducted to determine the dependence of biological activity on the chemical composition of various parts of the evening primrose, mainly leaves, stems, and seeds. Common components of all parts of the Oenothera biennis plants are fatty acids, phenolic acids, and flavonoids. In contrast, primrose seeds also contain proteins, carbohydrates, minerals, and vitamins. Therefore, it is believed that the most interesting sources of biologically active compounds are the seeds and, above all, evening primrose seed oil. This oil contains mainly aliphatic alcohols, fatty acids, sterols, and polyphenols. Evening primrose oil (EPO) is extremely high in linoleic acid (LA) (70–74%) and γ-linolenic acid (GLA) (8–10%), which may contribute to the proper functioning of human tissues because they are precursors of anti-inflammatory eicosanoids. EPO supplementation results in an increase in plasma levels of γ-linolenic acid and its metabolite dihomo-γ-linolenic acid (DGLA). This compound is oxidized by lipoxygenase (15-LOX) to 15-hydroxyeicosatrienoic acid (15-HETrE) or, under the influence of cyclooxygenase (COX), DGLA is metabolized to series 1 prostaglandins. These compounds have anti-inflammatory and anti-proliferative properties. Furthermore, 15-HETrE blocks the conversion of arachidonic acid (AA) to leukotriene A4 (LTA4) by direct inhibition of 5-LOX. In addition, γ-linolenic acid suppresses inflammation mediators such as interleukin 1β (IL-1β), interleukin 6 (IL-6), and cytokine - tumor necrosis factor α (TNF-α). The beneficial effects of EPO have been demonstrated in the case of atopic dermatitis, psoriasis, Sjögren’s syndrome, asthma, and anti-cancer therapy.